(untitled) (AYUSHDHARA, 2025)
Hydrosalpinx is a prominent cause of female infertility, frequently leading to tubal damage and occlusion. Standard modern interventions, such as prolonged antibiotics or surgical salpingectomy, carry limitations- either failing to resolve the condition or resulting in permanent loss of reproductive potential. This case report highlights the successful management of right-sided hydrosalpinx through an Ayurvedic approach in a 28-year-old female with primary infertility. Despite receiving conventional treatment, the patient showed no clinical or radiological improvement. Ultrasonography revealed a right fallopian tube dilated to 17.9mm, consistent with hydrosalpinx. Based on Ayurvedic assessment, the condition was understood as Kshetraja Vikriti caused by Kapha-Pitta Dushti, with localized Strotorodha in the reproductive tract. The treatment protocol included internal administration of Arogyavardhini Vati, Chandraprabha Vati, Triphala Guggulu, and Erand Bhrishta Haritaki, combined with intravaginal application of Yonivarti followed by Yoni Prakshalana. After three months, follow-up ultrasonography confirmed complete resolution of hydrosalpinx, with significant symptomatic improvement and no adverse effects. This outcome suggests that Yonivarti, offer a promising non-surgical alternative for managing tubal factor infertility.